Arrangement and Dynamication of Family Law Updating in Indonesia - Ike Yulisa; Muhamad Yusuf; Doli Witro; Luqyana Azmiya Putri; Mhd. Rasidin; Nurul Alamin (Al-'Adl, 2020)
In Indonesia, family law is well regulated in law or government regulations. In this case, with the increasingly complex family law issues supported by divorce rates, which reached 398,245 in 2015, then in 2017, it increased to 415,898, and with the development of science and technology, so many problems arise both in terms of muamalah or family law itself. For this reason, structuring is needed through legal reform that makes it follow what is needed by the wider community. Starting from this, this paper will discuss the arrangement of Islamic family law and the dynamics of family law reform in Indonesia. This study aims to provide an overview of the arrangement of Islamic families and Islamic family law reform in Indonesia. This paper uses qualitative research methods that are library researching. The data in this article was obtained from books, journals, articles, magazines related to the structure and dynamics of family law reforms in Indonesia. After the data is collected, the writer analyzes with data analysis techniques, namely data reduction, data presentation, and concluding. The results of the study show that the structure and dynamics of family law in Indonesia, when viewed in the context of Islamic law reform, reveal a unique and problematic portrait of reform. It is said so because Indonesia applies three legal systems, namely customary law, Islamic law, and Western law.